The Effect of Plant Distance on Forage Sorghum Numbu Varieties in Two Different Locations - Novrimansyah, Eko Abadi (PT ARRUS Intelektual Indonesia, 2024)
Sorghum is a plant belonging to the cereal group. It has the potential to be developed as a substitute food for rice. Has advantages related to water needs and tolerance for land that is experiencing drought. Sorghum is known for its tolerance to abiotic stress, especially in drought and hot weather. Environmental factors that influence sorghum growth include soil moisture and fertility, pests and diseases, abiotic stress, plant population, and weed competition, as well as planting distance. Sorghum plant growth can be grouped into three stages, namely, vegetative phase, reproductive phase, and seed formation and physiological maturity. This research aims to determine the yield of forage sorghum varieties of numbu with different planting distances and locations. This research was carried out in two district locations in Lampung Province, namely Central Lampung and Pringsewu. The materials used in this research were Numbu variety sorghum seeds, Urea fertilizer, KCl fertilizer, and SP-36 fertilizer. Meanwhile, the tools used in this research were tractors, hoes, measuring tapes, raffia ropes, corsets, jugs, back sprayers, rulers/meters, ovens, digital scales, hoses, sorghum harvester knives, crowbars, and SPAD 502 plus chlorophyll meters. The conclusion of this research is that the planting distance at two different locations in Lampung Province does not affect sorghum green yields, and the planting distance of 80cm x 20cm at the two research locations can be used to optimize agricultural land and increase farmer income.